A patient with Korsakoff syndrome of psychiatric and alcoholic etiology presenting as DSM-5 mild neurocognitive disorder [Corrigendum] - Nikolakaros G (Dove Medical Press, 2019)
Nikolakaros G, Kurki T, Myllymäki A, Ilonen T. Neuropsychiatr Dis Treat. 2019;15:1311–1320.   The author has advised that four errors have been detected in the reference list. Some of these issues were introduced hroughout the production process of this paper. The issues are outlined as follows: Read the original article